AKTUALISASI MODERASI BERAGAMA DALAM PENGEMBANGAN KURIKULUM PAI BERBASIS MERDEKA BELAJAR - Oktia Anisa Putri; Ifnaldi Nurmal (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This study aimed to learn how the implementation of religious moderation in the development of the PAI curriculum. Researchers used the Library Research research method with historical analysis research types and data collection techniques taken from various literature that discussed the theme in question to find out this. The data that has been collected is then analyzed using content analysis techniques. The study results reveal that the inculcation of moderation values ​​in education is so important in managing world civilization in the field of education. With a high sense of tolerance, will not blame differences. However, this does not mean that moderate Islamic teachings are wishy-washy. Still, these teachings will filter out existing disputes and unite the differences that divide the archipelago, nation and religion. Religious moderation in schools can be done through the Hidden Curriculum. The process of acculturation through the habit of internalization and institutionalization. The PAI curriculum now also uses the independent learning curriculum where the aim of the Free Learning curriculum is the policy of the Minister of Education and Culture to encourage students to master useful knowledge. and provide opportunities for students to be free but still express learning within existing limits and criticisms, without having to fade away as noble ideals and also morals for educators. The factors that influence religious moderation in schools include internal and external factors.